Psychometric evidence of the WHO-5 well-being index in a sample of participants from hospitals and older adults care centers in Peru - del Pilar Díaz Gamarra, Patricia; Rosario Quiroz, Fernando Joel; Alomía, Erika Roxana Estrada; Iparraguirre Yaurivilca, Noemí Edith; Misare Condori, Miguel Angel (Frontiers in Public Health, 2025)
IntroductionThe study of general well-being in older adulthood is of vital importance due to the negative repercussions of aging on daily life. Therefore, the objective of this research was to analyze the psychometric properties of the WHO-5 well-being index in a sample of participants from hospitals and older care centers in Peru.MethodA total of 661 older adults from Metropolitan Lima participated in the study (65% women and 35% men), aged between 60 and 93 years. They concurrently completed the WHO-5 well-being index and the Family APGAR.ResultsThe findings demonstrated adequate fit indices for the original five-item model: χ2/df = 3.73, CFI = 0.998, TLI = 0.995, SRMR = 0.03, and RMSEA = 0.06. Factor loadings were above 0.50. Convergent validity, assessed through Pearson’s correlation coefficient, was significant and direct (r = 0.35). Internal consistency indices (α = 0.84; ω = 0.84) were satisfactory. The unidimensional structure of the instrument was confirmed, as well as its measurement invariance across sexes.Discussion and conclusionsThe WHO-5 well-being index, when applied to older adults in Peru, confirms its unidimensional structure, demonstrates evidence of validity and reliability, and is an equivalent measure across sexes. This suggests its utility as a brief, reliable instrument for evaluating well-being in this population.